Antioxidants may reduce heterocyclic amines in commercially marinated beef steaks - F. Ameri; J. Scott Smith (Kansas Agricultural Experiment Station Research Reports, 2007)
Heterocyclic amines (HCAs) are carcinogenic and mutagenic compounds found at a level of parts per billion in grilled fish and meats. Since the connection between consumption of dietary carcinogens and risk of different cancers in humans has been established, it is necessary to explore effective inhibitors that can prevent or reduce the formation of HCAs in cooked meats. Cooking meat with natural antioxidants decreases or eliminates HCAs in meat. Our objective was to study the inhibition of five HCAs in beef steaks marinated using commercial ingredients that are natural antioxidants.
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Heterocyclic amines (HCAs); Steaks